A role for focal adhesion kinase in cardiac mitochondrial biogenesis induced by mechanical stress - Tornatore, Thais F.; Dalla Costa, Ana Paula; Clemente, Carolina F. M. Z.; Judice, Carla; Rocco, Silvana A.; Calegari, Vivian C.; Cardoso, Leandro; Cardoso, Alisson C.; Gonçalves, Anderson; Franchini, Kleber G. (American journal of physiology. Heart and circulatory physiology, 2011)
We studied the implication of focal adhesion kinase (FAK) in cardiac mitochondrial biogenesis induced by mechanical stress. Prolonged stretching (2–12 h) of neonatal rat ventricular myocytes (NRVM) upregulated the main components of mitochondrial transcription cascade [peroxisome proliferator-activated receptor coactivator-1 (PGC-1α), nuclear respiratory factor (NRF-1), and mitochondrial transcription factor A]. Concomitantly, prolonged stretching enhanced mitochondrial biogenesis [copy number of mitochondrial DNA (mtDNA), content of the subunit IV of cytochrome oxidase, and mitochondrial staining-green fluorescence intensity of Mitotracker green] and induced the hypertrophic growth (cell size and atrial natriuretic peptide transcripts) of NRVM. Furthermore, the stretching of NRVM enhanced phosphorylation, nuclear localization, and association of FAK with PGC-1α. Recombinant FAK COOH-terminal, but not the NH 2 -terminal or kinase domain, precipitated PGC-1α from nuclear extracts of NRVM. Depletion of FAK by RNA interference suppressed the upregulation of PGC-1α and NRF-1 and markedly attenuated the enhanced mitochondrial biogenesis and hypertrophic growth of stretched NRVM. In the context of energy metabolism, FAK depletion became manifest by a reduction of ATP levels in stretched NRVM. Complementary studies in adult mice left ventricle demonstrated that pressure overload upregulated PGC-1α, NRF-1, and mtDNA. In vivo FAK silencing transiently attenuated the upregulation of PGC-1α, NRF-1, and mtDNA, as well as the left ventricular hypertrophy induced by pressure overload. In conclusion, activation of FAK signaling seems to be important for conferring enhanced mitochondrial biogenesis coupled to the hypertrophic growth of cardiomyocytes in response to mechanical stress, via control of mitochondrial transcription cascade.